2017
DOI: 10.1039/c7nr04621a
|View full text |Cite
|
Sign up to set email alerts
|

Capacitive pressure sensing with suspended graphene–polymer heterostructure membranes

Abstract: We describe the fabrication and characterisation of a capacitive pressure sensor formed by an ultra-thin graphene-polymer heterostructure membrane spanning a large array of micro-cavities each up to 30 μm in diameter with 100% yield. Sensors covering an area of just 1 mm show reproducible pressure transduction under static and dynamic loading up to pressures of 250 kPa. The measured capacitance change in response to pressure is in good agreement with calculations. Further, we demonstrate high-sensitivity press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 63 publications
(75 reference statements)
0
46
0
1
Order By: Relevance
“…Apart from the rapid development demonstrated in this review, there is a bright future for tactile sensors utilizing smart materials (e.g., piezoelectric, self-healing, self-powering, self-cleaning), additive manufacturing, big data analytics (e.g., artificial intelligence) and cloud computing to fulfill healthcare demand for personalized medicine and remote monitoring. We found that sensitivity was the focus for most of the developed devices [247][248][249]251,[257][258][259][260][274][275][276][277][278][279][280][281][282][283][284][285] and those with piezoresistive mechanisms generally showed high performance when compared with others [242,259,271,283,293]. Although piezocapacitive-based sensors still show excellent detectability and sensitivity, they are more susceptible to noise resulting from field interaction and fringing capacitance, as well as, other factors such as temperature [192,247,294,614].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Apart from the rapid development demonstrated in this review, there is a bright future for tactile sensors utilizing smart materials (e.g., piezoelectric, self-healing, self-powering, self-cleaning), additive manufacturing, big data analytics (e.g., artificial intelligence) and cloud computing to fulfill healthcare demand for personalized medicine and remote monitoring. We found that sensitivity was the focus for most of the developed devices [247][248][249]251,[257][258][259][260][274][275][276][277][278][279][280][281][282][283][284][285] and those with piezoresistive mechanisms generally showed high performance when compared with others [242,259,271,283,293]. Although piezocapacitive-based sensors still show excellent detectability and sensitivity, they are more susceptible to noise resulting from field interaction and fringing capacitance, as well as, other factors such as temperature [192,247,294,614].…”
Section: Discussionmentioning
confidence: 97%
“…Graphene has been used with PI, such as a porous graphene (PG) sponge [276], interdigital electrode (IDE) [285] and with PU as rGO [281] or rGO with GO [273]. Furthermore, graphene has been used with materials such as silicon nitride in MEMS [274], PEN [278], PANI wrapped sponge [279], PMMA [277], DN hydrogels [280] and EcoFlex rubber [284]. Surprisingly, graphene has been also used with other unconventional materials such as tissue paper [275] polystyrene balls [283] and even a 3M VHB Tape [282].…”
mentioning
confidence: 99%
“…For these steps, the process simplicity and flexibility are determined by the selection of the sacrificial layers. The processing flow depicted in Figure 1 can be used for non-photosensitive polymeric sacrificial layers, metallic sacrificial layers or silicic ones [2,[13][14][15][16][17]. Other photoresist types can be used as sacrificial layers [6,8,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Механические свойства графена могут быть использованы для построения различных датчиков. Слабая устойчивость к изгибу листа графена может быть использована для построения высокочувствительных датчиков давления [8][9][10][11].…”
Section: Introductionunclassified